Kajian Missio Dei terhadap Tanggung Jawab Orang Percaya Berdasarkan 2 Korintus 5:18-20 - Rezky Alfero Josua; Well Therfine Renward Manurung; Eirenne Gracella Jeain Angela Imbir; Sumbut Yermianto (Sekolah Tinggi Teologi Jaffray Jakarta, 2023)
Missio Dei is the revelation of God himself as the one who loves the world. In this mission of God, God is both the Sender and the Sent One. Mission is not centered on the Church, but on God. With the sub-hermeneutic qualitative method: Exegesis, this article finds a missio Dei study of the responsibilities of believers based on 2 Corinthians 5:18-20. First, believers must do His work. Second, believers must spread His work. Third, believers must invite the reconciliation of others with Him in order to realize the goal of missio Dei, which is to establish Shalom (peace, no division, no loss and completeness) through the reconciliation that has occurred for believers, so that the faith community or Church as an agency of missio Dei must continue to carry out these three responsibilities to all people to receive reconciliation with God.